Design of a Coconut coir carbonization pilot plant - De la Rosa, Wilfredo; Bayani, Rogelio G.; Uriarte, Filemon A. Jr. (Diliman, Quezon City College of Engineering, 1965)
The feasibility of an actual commercial plant for the carbonization of coir dust to produce briquetted charcoal with the recovery of hydrogen gas, pyroligneous acid, tar and coconut fiber, based on pilot plant calculations has been established in this design report. The raw material for the plant is coconut husk. The main products are charcoal briquettes and hydrogen gas. The by-products are pyroligneous acid, tar, and baled fiber. Raw materials are available from the wastes of the copra processing. This pilot plant design is based on the data and results of the research conducted at the U.P. Industrial Research Center under the sponsorship of PHILCOA. This design report includes material and energy calculations, cost estimations, plant and equipment lay-outs and the break-even chart. The calculations show that the feasibility of constructing an actual commercial plant is good. Extensive economic analysis was conducted and the selection of the plant site for the actual commercial plant was carefully considered.
Plant design.
Typescript
Submitted in partial fulfillment of the requirements in ChE 62 Chemical Engineering Plant Design
Keywords: Factories--Design and construction; Coal--Carbonization.; Briquets (Fuel) industry; Coir